2024
DOI: 10.3390/cancers16040680
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Cancer’s Defense against Topoisomerase-Active Drugs: A Comprehensive Review

Nilesh Kumar Sharma,
Anjali Bahot,
Gopinath Sekar
et al.

Abstract: In recent years, the emergence of cancer drug resistance has been one of the crucial tumor hallmarks that are supported by the level of genetic heterogeneity and complexities at cellular levels. Oxidative stress, immune evasion, metabolic reprogramming, overexpression of ABC transporters, and stemness are among the several key contributing molecular and cellular response mechanisms. Topo-active drugs, e.g., doxorubicin and topotecan, are clinically active and are utilized extensively against a wide variety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 291 publications
0
2
0
Order By: Relevance
“…In cancer therapy, drug combination approach has been found to overcome the problems related to monotherapy and several studies have already demonstrated the superiority of combined therapies compared to monotherapy [ 83 ]. Combinations of small molecular inhibitors against specific DNA repair proteins and cytotoxic drugs have been suggested as future approach to achieve success in cancer treatment [ 84 ]. The identified drugs could have potential interactions with existing PCa treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer therapy, drug combination approach has been found to overcome the problems related to monotherapy and several studies have already demonstrated the superiority of combined therapies compared to monotherapy [ 83 ]. Combinations of small molecular inhibitors against specific DNA repair proteins and cytotoxic drugs have been suggested as future approach to achieve success in cancer treatment [ 84 ]. The identified drugs could have potential interactions with existing PCa treatments.…”
Section: Discussionmentioning
confidence: 99%
“…DNA damage-inducing therapies are fundamental in cancer treatment, as evidenced by the crucial roles of chemotherapy and radiotherapy, both of which operate by directly or indirectly inflicting DNA damage ( 89 ). These therapies can alter the DNA nucleotides, induce single-strand (SSBs) or double-strand breaks (DSBs), intercalate between bases, or form crosslinks within DNA or between DNA and proteins ( 90 94 ). Additionally, certain compounds induce DNA damage indirectly, e.g., by inhibiting the synthesis of deoxyribonucleotides ( 95 , 96 ).…”
Section: Dna Damage Resistance In Recurrent Cancer Cellsmentioning
confidence: 99%